PENGGUNAAN KECERDASAN BUATAN (ARTIFICIAL INTELEGENCE)DALAM PENDIDIKAN AGAMA KRISTEN DI ERA POSTHUMANIST - Herlina Barre Allo (Adisam Publisher, 2025)
Posthumanist education describes a transformation in the educational paradigm that involves the integration of technology, especially artificial intelligence (AI), in the context of Christianity. The application of artificial intelligence in Christian religious education brings significant changes in teaching approaches. AI enables personalization of learning tailored to each student's needs, creating an adaptive and inclusive learning environment. With intelligent algorithms, AI can help identify individuals' spiritual and intellectual needs, as well as provide relevant resources to deepen understanding of Christianity. Apart from that, the use of AI in text analysis and interpretation of holy books can provide a new perspective in understanding Christian religious teachings. Artificial intelligence systems can help decipher the complexity of sacred texts, provide historical and cultural context, and facilitate critical discussions to enrich students' understanding of religious teachings. However, the use of AI in Christian religious education also raises ethical questions. This paper discusses the ethical implications of this technology integration, including the role of teachers in the context of posthumanism, as well as the challenges and risks that may arise. Therefore, this paper puts forward recommendations for developing a balanced pedagogy, combining artificial intelligence with human wisdom to ensure holistic and meaningful Christian religious education in the era of posthumanism.